Anti-fungal activity of Morinda citrifolia (noni) extracts against Candida albicans: An in vitro study - K Barani; Sunayana Manipal; D Prabu; Adil Ahmed; Preethi Adusumilli; C Jeevika (Wolters Kluwer Medknow Publications, 2014)
Aim: The aim of this study was to investigate the anti-fungal activity of Morinda citrifolia fruit extract on Candida albicans. Materials and Methods: Juice extract from M. citrifolia fruit was lyophilized and used in anti-fungal testing. Anti-fungal activity of M. citrifolia fruit extract against C. albicans was tested in vitro at various concentrations. The inhibitory effect of M. citrifolia extract on C. albicans was determined by agar culture and applied broth dilution test. Results: M. citrifolia extract at 1000 μg/ml concentration effectively inhibited the growth of C. albicans (16.6 ± 0.3) compared with the positive control - amphotericin B (20.6 ± 0.6). It was found to be a dose-dependent reaction. Conclusion: M. citrifolia fruit extract had an anti-fungal effect on C. albicans and the inhibitory effect varied with concentration.